Numerical recording systems among the indigenous groups of southern Costa Rica - Rodríguez-Sánchez, Keilyn (2023)
The main objective of this document is to present indigenous notational systems, and their recent forms of usage, in three Chibchan towns in Costa Rica, an area where there were no empires or states during the pre-Columbian period, to associate the use of this recording technology with these types of political systems, as it has been done until recently. This is a qualitative and exploratory study. In Talamanca, there are records from 1875 to the present. Among Borucas, Ngöbes and Bribris, this practice had mainly a mnemonic use. Thanks to these results, we are left to analyze and rethink the association of this record form with the presence of states or empires in the archaeological past, and the possibility of creating recoding systems.